2014
DOI: 10.1017/s0022215114001601
|View full text |Cite
|
Sign up to set email alerts
|

Bone cement: how effective is it at restoring hearing in isolated incudostapedial erosion?

Abstract: Biocements can be successfully used to close isolated incudostapedial erosions. Larger comparative prospective studies documenting the length of eroded incus and types of reformation of the incudostapedial joint, with standardised reporting, are needed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…8 Several studies have shown that there was a considerable increase in the hearing quality of patients when the ossicular chain was rebuilt with GIC. [9][10][11][12] The ideal bone cement utilized for this objective ought to be moldable, effectively applied, quickly setting, nonpoisonous, fluid-resistant, fit for osteointegration, and ready to affect insignificant inflammation. 13 The present study aims to assess the use of GIC for the reconstruction of the long process of the incus.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several studies have shown that there was a considerable increase in the hearing quality of patients when the ossicular chain was rebuilt with GIC. [9][10][11][12] The ideal bone cement utilized for this objective ought to be moldable, effectively applied, quickly setting, nonpoisonous, fluid-resistant, fit for osteointegration, and ready to affect insignificant inflammation. 13 The present study aims to assess the use of GIC for the reconstruction of the long process of the incus.…”
Section: Introductionmentioning
confidence: 99%
“…Myringostapediopexy has been defined as a retraction of the tympanic membrane limited to the posterosuperior region, in which there is erosion of the long process of the incus and fixation of the affected tympanic segment to the stapes head. While it has been suggested that natural myringostapediopexy alone does not result in clinically relevant conductive hearing loss, discontinuity of the incudostapedial joint can cause significant conductive hearing loss requiring ossiculoplasty . A systematic review has shown the use of hydroxyapatite biocement is effective in closing air‐bone gap for these patients; however, this is generally an elective surgical procedure performed in the operating room …”
Section: Introductionmentioning
confidence: 99%
“…While it has been suggested that natural myringostapediopexy alone does not result in clinically relevant conductive hearing loss, discontinuity of the incudostapedial joint can cause significant conductive hearing loss requiring ossiculoplasty. 1,2 A systematic review has shown the use of hydroxyapatite biocement is effective in closing air-bone gap for these patients; however, this is generally an elective surgical procedure performed in the operating room. 2 A 24-year-old patient presented to the otology clinic at the UC Irvine Medical Center, Orange, CA with conductive hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…The use of bone cement to improve hearing in middle-ear surgery is well known 3 , 4 . Ardıç et al 5 .…”
mentioning
confidence: 99%